2014
DOI: 10.1371/journal.pone.0114009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MicroRNAs Linked to Regulators of Muscle Protein Synthesis and Regeneration in Young and Old Skeletal Muscle

Abstract: BackgroundOver the course of ageing there is a natural and progressive loss of skeletal muscle mass. The onset and progression of age-related muscle wasting is associated with an attenuated activation of Akt-mTOR signalling and muscle protein synthesis in response to anabolic stimuli such as resistance exercise. MicroRNAs (miRNAs) are novel and important post-transcriptional regulators of numerous cellular processes. The role of miRNAs in the regulation of muscle protein synthesis following resistance exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 51 publications
4
78
1
3
Order By: Relevance
“…miRNAs have been associated with the regulation of skeletal muscle mass (49), and their expression levels are altered following both single bouts of exercise (31,72,91) and short-term exercise training (26,72). However, no studies have investigated whether miRNA expression is altered following concurrent compared with single-mode RE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs have been associated with the regulation of skeletal muscle mass (49), and their expression levels are altered following both single bouts of exercise (31,72,91) and short-term exercise training (26,72). However, no studies have investigated whether miRNA expression is altered following concurrent compared with single-mode RE.…”
Section: Discussionmentioning
confidence: 99%
“…Given their purported role in posttranscriptional regulation, miRNAs have emerged as a potential regulator of exercise-induced adaptations in skeletal muscle (90). The expression of various miRNA species in human skeletal muscle is altered following both single bouts of exercise (31,72,91) and after short-term exercise training (26,72). miRNAs have been implicated in the regulation of the IGF-1/Akt, Fox-O1, and myogenesis pathways, all known to play a role in RE-induced adaptations in skeletal muscle (49), although the direct impact of miRNAs on these pathways in response to RE is yet to be experimentally validated.…”
mentioning
confidence: 99%
“…Greater insight into interactions between the many forms of RNAs and proteins that regulate muscle growth and maintain homeostasis, is of central importance to livestock industries related to improvement of meat quality and production using molecular approaches (Hou et al, 2012;Li et al, 2012) and to clinical muscle disorders. For example, many ncRNAs have been identified in cases of aberrant muscle growth and muscle atrophy, including genetic diseases as Duchenne muscular dystrophy (Neguembor et al, 2014;Twayana et al, 2013), inflammatory conditions like cachexia (Soares et al, 2014) and age-related muscle wasting (Drummond et al, 2011); therapeutic modulation of many ncRNAs by exercise has recently been demonstrated (Zacharewicz et al, 2014). The ncRNAs are likely to represent viable therapeutic targets, or useful readouts of treatment efficacy or disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Many beneficial effects of physical exercise have been reported: a) improvement of plasma lipid composition (decreased triglyceride; total cholesterol and LDL-cholesterol; and increased HDL-cholesterol levels), b) amelioration of glucose homeostasis (elevated insulinindependent glucose uptake; glucose transporter-4 (GLUT-4) expression; and insulin sensitivity); c) increased skeletal muscle oxidative capacity (improved biogenesis and mitochondrial metabolism), and d) reduction in inflammation markers [74,[79][80][81][82][83]. Physical exercise modulates expression of several miRs involved in protein synthesis, such as miR26a, miR-29a, miR-378, miR-451, and miR-696 [84][85][86]. However, the mechanisms involved are not fully known yet.…”
Section: Physical Exercise and Gene Expressionmentioning
confidence: 99%